Recent Advances in Self-Healing Green Composites for Structural Applications - Khan, Sher Wali; Tariq, Muhammad (New Environmentally-Friendly Materials, 2022)
The development of self-healing green composites offers a sustainable pathway to extend the lifespan of structural materials while reducing environmental impact. This review takes a look at developments in the three principal techniques of self-healing considered namely use of bio-based healing agents, use of microcapsule systems, and also use of vascular networks with particular reference to application in structural engineering set ups. Renewable-based repair materials in the form of bio-based healing agents offer a green-friendly repair agent but limit rebound in the speed of reaction and in stability. Microcapsule systems provide self-contained, readily incorporated repair abilities, but are usually restricted in being used once only. Biologically inspired, vascular networks allow repeatable and even sustained repair, but their manufacturing is more complex requiring careful optimization of the overall network. Each strategy is discussed in terms of material composition, healing mechanisms, advantages, limitations, and recent innovations. The review concludes with a comparative analysis and highlights future directions, including hybrid healing systems, nanomaterial enhancements, and integration with structural health monitoring. These advances underscore the potential of self-healing green composites to meet the dual demands of high performance and environmental responsibility in next-generation structural applications.